Study on humic acid derived from EFB based vermicompost as biopesticide - Khiew, A.A.M. (Institute of Physics Publishing, 2020)
The increment of global population by 1.1 annually demands higher agricultural yield to ensure sustainable food source which leads to intensive usage of chemical fertilizer and pesticide. However, this practice poses various environmental and health problems which ultimately encourages the development of safer organic fertilizers and bio-pesticides. One potential method is to utilize Humic Acid (HA), a natural plant's growth promoter, present in organic compost as an environmental-friendly fertilizer as well as insect control agent. This study investigated the effectiveness of HA extracted from vermicompost of Palm Oil Empty Fruit Bunches (EFB) as biopesticide. HA was extracted from the vermicompost via alkaline extraction followed by precipitation in strong acid that resulted in HA mass yield of 2.336. The insect repellent ability of HA, Garlic Extract (GE) and 87 GE + 13 HA was investigated by spraying the solution onto soil samples in the presence of crickets. The effectiveness of the insect control agents was determined by recording the number of crickets avoiding the infected area. The test revealed that the insects exhibited most repulsive behavior towards 87 GE + 13 HA, followed by HA and lastly GE. The results indicate that HA has the potential to be used as biopesticide, with higher prospect when combined with GE. The dual benefits of HA utilization as plant growth promoter and insect repellent promise a more sustainable approach towards modern agriculture. Â© Published under licence by IOP Publishing Ltd.